Pengaruh independensi auditor, pengalaman kerja auditor, kompetensi auditor dan tekanan anggaran waktu terhadap kualitas audit - Savitri Dewi, Lely; Katuruni, Innas Susantira; Rubianti, Nur Fitria (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2025)
This study aims to examine the extent of the influence of auditor independence, auditor work experience, auditor competence, and time budget pressure on audit quality at the Public Accounting Firm (KAP) in Bandung City. This study uses a quantitative approach with data collection techniques through distributing questionnaires to auditors who work at the KAP. The variables studied include independence, work experience, competence, and time budget pressure, with audit quality as the dependent variable. The test results show that partially, each variable of independence, work experience, competence, and time budget pressure has no significant effect on audit quality. However, the simultaneous test results prove that the four variables together have a significant effect on audit quality. This finding shows that audit quality is not determined by one factor alone, but by a combination of several factors that support each other. Therefore, improving audit quality can be achieved through strengthening the synergy between technical competence, experience, independence, and auditor time management in the audit implementation process.